2023
DOI: 10.1038/s41598-023-29072-3
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of four endemic human coronaviruses and, reactivity and neutralization capability against SARS-CoV-2 among children in the Philippines

Abstract: Four endemic human coronaviruses (HCoV), HCoV-229E, HCoV-NL63, HCoV-HKU1, and HCoV-OC43, are closely related to SARS-CoV-2. These coronaviruses are known to infect humans living in temperate areas, including children under 5 years old; however, the seroprevalence of four HCoVs among children in tropical areas, including the Philippines, remains unclear. This study aimed to assess the prevalence of antibodies against four HCoVs and to determine the reactivity and neutralization of these antibodies against SARS-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Among the subtype of sCoVs, 229E and OC43 were the most widely distributed, with seroprevalence of 78.5% and 75.1%, respectively. These findings are comparable to another study conducted in Canada that showed the seroprevalence of 82.9% for OC43 and 82.1% for 229E ( 22 ).Considering the high prevalence of anti-sCoVs immunity in the general population,immune imprinting should be an important issue to further optimize the strategy for the mass vaccination against SARS-CoV-2 infections ( 23 25 ). However, the interaction between pre-existing anti-sCoVs immunity and SARS-CoV-2 specific immune responses remains elusive.…”
Section: Discussionsupporting
confidence: 80%
“…Among the subtype of sCoVs, 229E and OC43 were the most widely distributed, with seroprevalence of 78.5% and 75.1%, respectively. These findings are comparable to another study conducted in Canada that showed the seroprevalence of 82.9% for OC43 and 82.1% for 229E ( 22 ).Considering the high prevalence of anti-sCoVs immunity in the general population,immune imprinting should be an important issue to further optimize the strategy for the mass vaccination against SARS-CoV-2 infections ( 23 25 ). However, the interaction between pre-existing anti-sCoVs immunity and SARS-CoV-2 specific immune responses remains elusive.…”
Section: Discussionsupporting
confidence: 80%
“…We observed high seroprevalence to the four endemic hCoVs in adolescents in the Philippines before the COVID-19 pandemic, suggesting intense circulation in this population. A recent study also showed young children in Biliran, Philippines hospitalized with severe respiratory infections before the COVID-19 pandemic had high seroprevalence to all four hCoVs, indicating a high attack rate [37]. Previous studies in the USA, Germany, Hong Kong, and China have observed high seroprevalence to the hCoVs in children over age 10 (over 50%), with higher levels to OC43 and 229E, and similar levels to those observed in older adults [4].…”
Section: Discussionmentioning
confidence: 66%
“…The endemic human coronaviruses (HCoVs) circulate seasonally and generally cause mild common cold like symptoms. Seroprevalence studies suggest most people have encountered one or more HCoVs in childhood by the age of 5 1 3 . Several studies have reported high levels of HCoV reactive antibodies in critically ill or deceased Coronavirus disease 2019 (COVID-19) patients, suggesting a detrimental effect of HCoV cross-reactive antibodies on clinical outcomes 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%